Mixed Endocrine Somatostatinoma of the Ampulla of Vater Associated with a Neurofibromatosis Type 1: A Case Report and Review of the Literature - Deschamps, Lydia; Dokmak, Safi; Guedj, Nathalie; Ruszniewki, Philippe; Sauvanet, Alain; Couvelard, Anne (JOP. Journal of the Pancreas, 2016)
Context Mixed endocrine tumors are double neoplasms with both glandular and endocrine components; these tumors are rare, especially those arising in the ampulla of Vater. Ampullary somatostatinomas are classically associated with neurofibromatosis type 1. We herein describe the first reported case of a mixed endocrine somatostatinoma of the ampulla of Vater associated with neurofibromatosis type 1; we also present a review of the literature of the 7 mixed endocrine tumors of the ampulla which have been reported so far. Case report A 49-year-old woman presented with atypical abdominal pain. Endoscopic examination revealed a tumor involving the ampulla of Vater and a CT scan identified stenoses of both the distal common bile duct and the main pancreatic duct. A pancreaticoduodenectomy was performed and pathological examination revealed two tumor components, exocrine (high grade adenoma with infiltrative adenocarcinoma) and endocrine (expressing somatostatin hormone) with lymph node metastases originating from both types. The patient was treated with adjuvant chemotherapy and has had no recurrence for 3 years. Discussion In ampullary somatostatinomas, psammoma bodies are pathognomonic and chromogranin A is rarely expressed: these features should alert the pathologist to an association with neurofibromatosis type 1. The management of patients with mixed tumors is challenging. The treatment of choice is surgery, and adjuvant chemotherapy should be adapted to the most aggressive component, i.e. the exocrine one. Conclusion Because of their rarity, the diagnosis of ampullary mixed endocrine tumors is difficult. Our case points out the characteristic features of these neoplasms and their possible association with neurofibromatosis type 1. Image: Large exophytic duodenal tumor situated in and around the ampulla of Vater.